(untitled) (The Review of Diabetic Studies, 2025)
Background: Dental assistants are essential members of the dental care team, yet their work often involves prolonged static postures, repetitive movements, and close patient contact, predisposing them to a range of occupational hazards. In Saudi Arabia, musculoskeletal disorders (MSDs) are particularly prevalent, alongside environmental, biological, and psychosocial risks. While global best practices offer effective solutions, their application locally faces several challenges. Objective: This narrative review synthesizes evidence on the ergonomic challenges and occupational hazards faced by dental assistants in Saudi clinics, examines international best practices, and proposes targeted prevention strategies adapted to the Saudi healthcare context. Methods: A narrative review approach was used, drawing on peer-reviewed studies from Saudi Arabia and relevant international literature. Data sources included PubMed, Scopus, Google Scholar, and Ministry of Health publications, focusing on studies addressing MSD prevalence, ergonomic risk factors, intervention outcomes, and policy frameworks. Results: Saudi studies report MSD prevalence rates exceeding 80% among dental assistants, with the lower back, neck, shoulders, and upper back most affected. Contributing factors include inadequate workstation design, inconsistent ergonomic training, and high patient loads. International interventions—such as adjustable equipment, micro-break programs, task rotation, and participatory ergonomics—have demonstrated significant benefits but require cultural, financial, and organizational adaptation for Saudi settings. Conclusion: The occupational health of Saudi dental assistants can be significantly improved through an integrated approach combining policy reform, clinic-level ergonomic interventions, and continuous professional training. Adapting global best practices to the local context is crucial to reducing injury rates, enhancing job satisfaction, and improving patient care outcomes. Implications: Policymakers, clinic managers, and educators should collaborate to enforce ergonomic standards, modernize equipment, and integrate ergonomics into dental assistant education to ensure sustainable improvements in workplace health.